Global Impact of Pandemic on Automobile Sector and Its Solution Through Digital Marketing - Kaur, Gulreet (Digital Repository of Theses, 2025)
The COVID-19 pandemic has significantly impacted the global automobile sector, leading to disruptions in manufacturing, supply chains, and consumer behavior. This research investigates the effects of the pandemic on the industry and proposes digital marketing strategies as a solution to mitigate these challenges. The study employs a mixed-methods approach, combining qualitative and quantitative methodologies. Primary data is collected through interviews and surveys with key stakeholders, including manufacturers, dealers, and consumers. Secondary data is obtained from industry reports, academic literature, and online databases. The findings reveal that the pandemic has caused temporary closures of production plants, shortages of critical components, and decreased demand for new vehicles. To address these challenges, digital marketing is proposed as a solution. Digital platforms offer manufacturers and dealers the ability to connect with customers, build brand awareness, and influence purchasing decisions through targeted online campaigns. Virtual showrooms and online test drives enhance the accessibility and convenience of automobile sales, while also aiding in inventory management and cost reduction. The research concludes that digital marketing strategies can help the automobile sector navigate the challenges posed by the pandemic. The study contributes to the existing body of knowledge by providing empirical evidence on the global impact of the pandemic on the automobile industry and offering insights into the practical implications of employing digital marketing solutions to recover and thrive in a post-pandemic environment. Keywords: COVID-19, pandemic, automobile sector, digital marketing, global impact, manufacturing, supply chain, consumer behavior, online advertising, virtual showrooms, mixed-methods approach